2019
DOI: 10.3390/en12071198
|View full text |Cite
|
Sign up to set email alerts
|

Pelleting of Pine and Switchgrass Blends: Effect of Process Variables and Blend Ratio on the Pellet Quality and Energy Consumption

Abstract: The blending of woody and herbaceous biomass can influence pellet quality and the energy consumption of the process. This work aims to understand the pelleting characteristics of 2-inch top-pine residue blended with switchgrass at high moisture content. The process variables tested are blend moisture content, length-to-diameter (L/D) ratio in the pellet die, and the blend ratio. A flat die pellet mill was also used in this study. The pine and switchgrass blend ratios that were tested include: (1) 25% 2-inch to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 44 publications
6
40
2
Order By: Relevance
“…The moisture content in the investigated pellets varied from 3.0% for pine pellets to ca. 20% for post-hydrolytic wood pellets, which was in the range of optimal values indicated by other researchers [49].…”
Section: Technical and Chemical Characteristicssupporting
confidence: 69%
“…The moisture content in the investigated pellets varied from 3.0% for pine pellets to ca. 20% for post-hydrolytic wood pellets, which was in the range of optimal values indicated by other researchers [49].…”
Section: Technical and Chemical Characteristicssupporting
confidence: 69%
“…Response surface methodology (RSM) is used to approximate the implicit limit state function by the polynomial function through a series of deterministic experiments [41]. RSM is a mathematical modeling tool for predicting the output relationship under multiple input parameters.…”
Section: Analysis Of Response Surface Methodologymentioning
confidence: 99%
“…Several studies reported the pelleting of different types of biomass and their blends, with most of the studies focusing on material and process parameters including the mechanism of bonding from different viewpoints [2,[23][24][25][26][27]. Despite the numerous studies, the exact mechanism involved in bonding in biomass pellets and the source of inter-particle bonding relevant to pellet quality are not fully understood and still a subject of debate, particularly when the pellets are made from a blend of two or more different biomass materials.…”
Section: Purpose Of Studymentioning
confidence: 99%